No evidence for incipient speciation by selfing in North American Arabidopsis lyrata. (14th July 2021) - Gorman, Courtney E.; Li, Yan; Dorken, Marcel E.; Stift, Marc
Abstract: Self‐fertilization inherently restricts gene flow by reducing the fraction of offspring that can be produced by inter‐population matings. Therefore, mating system transitions from outcrossing to selfing could result in reproductive isolation between selfing and outcrossing lineages and provide a starting point for speciation. In newly diverged lineages, for example after a transition to selfing, further reproductive isolation can be caused by a variety of prezygotic and post‐zygotic mechanisms that operate before, during and after pollination. In animals, prezygotic barriers tend to evolve faster than post‐zygotic ones. This is not necessarily the case for plants, for which the relative importance of post‐mating, post‐fertilization and early‐acting post‐zygotic barriers has been investigated far less. To test whether post‐pollination isolation exists between populations of North American Arabidopsis lyrata that differ in breeding (self‐incompatible versus self‐compatible) and mating system (outcrossing versus selfing), we compared patterns of seed set after crosses made within populations, between populations of the same mating system and between populations with different mating systems. We found no evidence for post‐pollination isolation between plants from selfing populations (self‐compatible, low outcrossing rates) and outcrossing populations (self‐incompatible, high outcrossing rates) via either prezygotic or early‐acting post‐zygotic mechanisms. Together with the results of other studies indicating the absence of reproductive barriers acting before and during pollination, we conclude that the transition to selfing in this study system has not led to the formation of reproductive barriers between selfing and outcrossing populations of North American A .  lyrata . Abstract : Photo of Arabidopsis lyrata (Photo credit: Marc Stift). This species displays intraspecific breeding and mating system variation in its North American populations.